Historical place of Prainha of Vila Velha/ES: Insider and a close-up view - Oliveira, Melissa Ramos da Silva; Pinheiro, Victória Christina Simões (Technical and Scientific Journal Green Cities, 2021)
Memory contributes to maintaining the cultural heritage present in the history of a people, but how does this affective relationship between user and the space? The objective of this article is to investigate, with the application of online questionnaires about Prainha for a general and specific public, how the brain mechanisms – memory, attention and feelings – are activated in the process of recognition of the cultural assets of the historical site of Prainha. Using questionnaires, we investigated the people’s memories and how they can impact the preservation of the historic site. The results showed that memories are a source of life for history itself. KEY-WORDS: Prainha, Cultural Heritage, Memory, Affective Relationship.